Fulfilment of Formal Education for Children with Criminal Sentences: Analysis of Law Number 11 of 2012 concerning the Juvenile Justice System - Subarsyah Subarsyah (AL-ISHLAH: Jurnal Pendidikan, 2021)
Crimes committed by children are currently experiencing a very significant increase. In Indonesia, the settlement of criminal cases against children is included in vulnerable children who need more attention in fulfilling their rights. However, there are still many violations of children's rights during their status as perpetrators of crimes and afterwards. This study aims to analyze the fulfilment of the formal education of criminal children by Law Number 11 of 2012 concerning the Juvenile Justice System. This study uses a qualitative approach with a literature study. The results of the study explain that Indonesia as a country that has ratified the Convention on the Rights of the Child through Presidential Decree Number 36 of 1990 dated August 25, 1990, has further integrated children's rights into national law, namely into Law Number 23 of 2002 concerning Child Protection. Protection of children was created as an effort to educate and build quality and affluent children in education. These forms of protection include providing comfort, security, health, and adequate education. The existence of The Child Special Guidance Institute plays a vital role in fulfilling the educational needs of formal and non-formal children.